Molecular Detection of the Gene Encoding Second Internal Transcribed Spacer of Sarcoptes scabiei in Rabbits in Several Regions in East Java - Rusdiana, Nur; Retno Lastuti, Nunuk Dyah; Aisyah, Siti; Purwanti, Ni Luh Lasmi; Sewoyo, Palagan Senopati (Universitas Syiah Kuala, 2023)
This study aimed to detect the Second Internal Transcribed Spacer (ITS-2) encoding gene of Sarcoptes scabiei from rabbits. ITS-2 is a highly conserved gene and always used to identify and differentiate host species infected by S. scabiei. Isolates of S. scabieiwere collected from samples of rabbit skin scrapings suspected of being infected with S. scabiei. The rabbits were acquired from Surabaya, Sidoarjo, Pasuruan, Mojokerto and Nganjuk. Detection on the presence of S. scabiei was carried out microscopically then further confirmed by PCR method and visualized using electrophoresis. PCR identification results showed DNA bands at 304 base pairs. The results showed that samples were infected by S. scabiei, determined by the presence of ITS-2 encoding gene. The ITS-2 encoding gene was chosen as the main focus in this study because it was easily amplified that made analysis and identification easier. The high cases of scabies in Indonesia can be a warning to prevent infection of S. scabiei, especially in pets that have the potential as a reservoir in spreading diseases.